The V‐ATPase is expressed in the choroid plexus and mediates cAMP‐induced intracellular pH alterations. Issue 1 (4th January 2017) - Christensen, Henriette L.; Păunescu, Teodor G.; Matchkov, Vladimir; Barbuskaite, Dagne; Brown, Dennis; Damkier, Helle H.; Praetorius, Jeppe
Abstract: The cerebrospinal fluid (CSF) pH influences brain interstitial pH and, therefore, brain function. We hypothesized that the choroid plexus epithelium (CPE) expresses the vacuolar H + ‐ATPase (V‐ATPase) as an acid extrusion mechanism in the luminal membrane to counteract detrimental elevations in CSF pH. The expression of mRNA corresponding to several V‐ATPase subunits was demonstrated by RT‐PCR analysis of CPE cells (CPECs) isolated by fluorescence‐activated cell sorting. Immunofluorescence and electron microscopy localized the V‐ATPase primarily in intracellular vesicles with only a minor fraction in the luminal microvillus area. The vesicles did not translocate to the luminal membrane in two in vivo models of hypocapnia‐induced alkalosis. The Na + ‐independent intracellular pH (pHi ) recovery from acidification was studied in freshly isolated clusters of CPECs. At extracellular pH (pHo ) 7.4, the cells failed to display significant concanamycin A‐sensitive pHi recovery (i.e., V‐ATPase activity). The recovery rate in the absence of Na + amounted to <10% of the pHi recovery rate observed in the presence of Na + . Recovery of pHi was faster at pHo 7.8 and was abolished at pHo 7.0. The concanamycin A‐sensitive pHi recovery was stimulated by cAMP at pH 7.4 in vitro, but intraventricular infusion of the membrane‐permeant cAMP analog 8‐CPT‐cAMP did not result in trafficking of the V‐ATPase. In conclusion, we find evidence for the expression of a minor fraction of V‐ATPase in the luminal membrane of CPECs. This fraction does not contribute to enhanced acid extrusion at high extracellular pH, but seems to be activated by cAMP in a trafficking‐independent manner. Abstract : We hypothesized that the choroid plexus epithelium expresses the V‐ATPase as an acid extrusion mechanism in the luminal membrane. Several V‐ATPase subunits were detected and only a minor fraction of the protein was localized to the microvilli. The cells displayed significant concanamycin A‐sensitive pH recovery (i.e., V‐ATPase activity) only after stimulation by cAMP in a trafficking‐independent manner.